The healthcare burden of isolated aortic valve insufficiency - Ibrahim Sultan; Michael Ryan; Candace Gunnarsson; Natalie Heidrich; Prashanth Vallabhajosyula (Scientific Reports)
Abstract To analyze and compare the differences in mortality, healthcare utilization, and costs between patients with symptomatic and asymptomatic isolated aortic insufficiency (AI). We utilized Optum United Health Care Database for US patients who had an AI claim between 2017 and 2022, with 12 months of continuous enrollment (baseline period) prior to diagnosis. Exclusion criteria were AVR during the baseline period or a diagnosis of aortic stenosis. Patients were split into two cohorts: those with symptoms (SAI) and those without (AAI). SAI patients had ≥ 2 visits for heart failure, angina, dyspnea, or syncope at baseline. Outcomes of interest were all-cause mortality, time to home health, time to SNF, annualized healthcare utilization, and annualized costs. We used the Cox proportional model to estimate mortality and general linear models to estimate healthcare utilization and costs. Outcomes were modeled separately. Of 249,660 patients, 58.23% were symptomatic; they were generally older and sicker than the AAI cohort, and less than 1% received AVR. Almost half of AAI patients were estimated to develop symptoms within 5 years post-diagnosis. SAI outcomes were consistently higher across all measured outcomes. SAI patients have higher mortality, healthcare utilization, and costs than AAI. However, AI can progress quickly from asymptomatic to symptomatic. Early detection and timely interventions to slow the progression or address it surgically should be emphasized to limit the impact of AI.